COMPARATIVE EVALUATION OF FISH PROTEIN CONCENTRATE AND FUNCTIONAL FISH PROTEIN CONCENTRATE FROM CAT FISH. - GOPAKUMAR, K; SHENOY, A VASANTH (Fishery Technology, 2017)
Fish protein concentrate and functional fish protein concentratesamples were prepared from eviscerated meat of cat fish(Tachysurus jella Day). Functional fish protein concentrate isfound to be lighter, less gritty and rehydrates more rapidlythan fish protein concentrate. Functional FPC is seen to havehigher PER and biscuits containing it at levels of 5 and 7percent are less hard compared to FPC.